Proof of Adultery: An Islamic Legal Perspective on the Dilemma Between Norms and Human Dignity - Apriyanti, Apriyanti (Islam Realitas: Journal of Islamic and Social Studies, 2023)
Allegations of brutality in the Islamic penal code significantly damage the reputation of Islam globally. The imposition of one hundred lashes as a punishment for individuals who engage in adultery can only occur if there is legal evidence to substantiate the act of adultery. The purpose of this article is to demonstrate the extent to which Islamic criminal law upholds human dignity, particularly in some cases involving individuals accused of adultery. This study adopts a normative perspective, employing an Islamic legal framework. The research collected primary and secondary data from various sources, including fiqh's books, hadith’s books, books on human rights and dignity, journals, and other articles. The Bayani method will be employed to analyze all data. Research findings indicate that adultery can be proven through three methods: the testimony of four witnesses, the confession of the perpetrator, and evidence of pregnancy. Nevertheless, in practice, achieving these three forms of evidence can be exceedingly challenging, as the fundamental tenet of Islamic penal code is to refrain from imposing penalties in cases that remain doubtful (shubhat). Islam places great significance on human rights, human dignity, and human worth.Tuduhan kejam pada hukum pidana Islam secara signifikan merusak reputasi Islam secara global. Penjatuhan hukuman cambuk sebanyak seratus kali bagi pelaku zina hanya dapat terjadi apabila terdapat bukti-bukti sah yang membenarkan perbuatan zina tersebut. Artikel ini ditujukan untuk menunjukkan sejauh mana hukum pidana Islam menjunjung tinggi harkat dan martabat manusia, khususnya dalam kasus-kasus yang melibatkan individu yang dituduh melakukan perzinahan. Penelitian ini berbentuk normatif, dengan menggunakan kerangka hukum Islam. Penelitian ini mengumpulkan data primer dan sekunder dari berbagai sumber antara lain buku-buku fiqih, kitab-kitab hadis, buku hak asasi dan martabat manusia, jurnal, dan artikel. Metode bayani akan digunakan untuk menganalisis seluruh data. Temuan penelitian menunjukkan bahwa perzinahan dapat dibuktikan melalui tiga cara: keterangan empat orang saksi, pengakuan pelaku, dan bukti kehamilan. Namun demikian, dalam praktiknya, mewujudkan ketiga bentuk bukti ini bisa jadi sangat menantang dan sulit, karena prinsip dasar pidana Islam adalah menghindari untuk menjatuhkan hukuman dalam kasus-kasus yang masih diragukan (shubhat). Islam sangat mementingkan hak asasi manusia, harkat dan martabat manusia.